1984
DOI: 10.1148/radiology.150.1.6689793
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of brain tumors: measurement of T1. Work in progress.

Abstract: Longitudinal relaxation times (T1) of 20 brain tumors were calculated in vivo using a whole-body magnetic resonance unit with a 0.15-T resistive magnet. Images employing standard inversion recovery pulse sequences with different intervals between the 180 degrees pulse and selective excitation pulses were compared on every point of the 256 X 256 pixel matrix. Tumor, white matter, and gray matter were sampled from each patient from the computed T1 image for T1 measurement. Astrocytomas, neurinomas, and metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Note that Oo in Eq. [2] is only a rough, system-calibrated guess of the flip-angle, whereas a,,a(r)B,, is the actual flip-angle experienced at position r.…”
Section: Theorymentioning
confidence: 99%
“…Note that Oo in Eq. [2] is only a rough, system-calibrated guess of the flip-angle, whereas a,,a(r)B,, is the actual flip-angle experienced at position r.…”
Section: Theorymentioning
confidence: 99%
“…12 in whom the interval between the first CT examination with contrast medium of progression, in terms of the extent of the low attenuating area, or of alteration of the signs of mild expansion that was seen in the primary CT examination without contrast medium. Table 4 Signal intensity values and ratio of signal intensity between tumour and white matter (T/W) in high-grade astrocytomas (cases [1][2][3][4][5], low-grade astrocytomas (cases 8 In cases 8 and 13, where no enhancement was noted after administration of contrast medium on MR or CT, the ROI was placed according to the area of methionine accumulation in PET.…”
Section: Methodsmentioning
confidence: 99%
“…Although several authors (1,5,24) have found abnormalities in T1 and T2 relaxation times in intracranial tumours, the values alone have not been sufficient for separating tumour tissue from oedema or for distinguishing benign from malignant lesions. The need for a contrast agent (marker of blood-brain-barrier (BBB) disruption; 29) in MR that could cause changes in T1 and T2, facilitating tumour/oedema discrimination, was pointed out (3).…”
mentioning
confidence: 98%
“…In 1984, the first two articles (48,49) dealing with MR imaging of brain tumors appeared in Radiology. In the first report (48), T1 measurements of brain masses were performed, and the authors found that astrocytomas had the longest T1 and lipomas had the shortest. The second article (49) was a comparison between the then well-established CT and MR imaging.…”
Section: Early Physiologic Tumor Neuroimagingmentioning
confidence: 99%